The Influence of Good Corporate Governance, Firm Size, and Capital Structure on Financial Performance in PT pertamina Patra Niaga - Assyaroful Akbar, Zuhdan Rhazes; Rangkuti, Muhammad Ihsan (Jurnal Mantik, 2025)
This study investigates the influence of Good Corporate Governance (GCG), firm size, and capital structure on the financial performance of PT Pertamina Patra Niaga. As a vital player in Indonesia’s energy sector, understanding the determinants of financial performance in this state-owned enterprise is critical for policy formulation and strategic planning. Employing a quantitative research method with secondary data from financial reports spanning 2020-2025, the analysis applies multiple linear regression to examine the relationships among variables. The findings reveal that GCG has a significant and positive impact on financial performance, supporting agency theory which emphasizes the role of governance in aligning interests between management and stakeholders. Firm size also demonstrates a significant influence, suggesting that larger firms benefit from economies of scale and greater market access. Moreover, capital structure exhibits a notable effect, indicating the importance of optimal debt-equity balance in enhancing profitability. These results provide valuable insights for corporate managers, regulators, and investors in strengthening governance mechanisms and financial strategies to boost organizational performance in the energy sector.